2013
DOI: 10.1007/s10773-013-1693-1
|View full text |Cite
|
Sign up to set email alerts
|

The Isotopic Field-Charge Assumption Applied to the Electromagnetic Interaction

Abstract: This paper applies the isotopic field-charge spin theory (Darvas, IJTP 2011) to the electromagnetic interaction. First there is derived a modified Dirac equation in the presence of a velocity dependent gauge field and isotopic field charges (namely Coulomb and Lorentz type electric charges, as well as gravitational and inertial masses). This equation is compared with the classical Dirac equation. There is shown that, since the presence of isotopic fieldcharges would distort the Lorentz invariance of the equati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…This paper extends the field theoretic model of the electromagnetic interaction started in [17] (cf., footnote 1 in [17]). To remember, [17] introduced the isotopic electric charges in the classical Maxwell EM theory and showed that -applied in itself alone -the presence of isotopic electric charges would destroy the Lorentz invariance of the Maxwell theory. To restore the broken invariance, we applied the conservation of the isotopic field-charge spin, proven in [10], so that the two transformations executed together ensure the invariance and save the physical relevance of our theory.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…This paper extends the field theoretic model of the electromagnetic interaction started in [17] (cf., footnote 1 in [17]). To remember, [17] introduced the isotopic electric charges in the classical Maxwell EM theory and showed that -applied in itself alone -the presence of isotopic electric charges would destroy the Lorentz invariance of the Maxwell theory. To restore the broken invariance, we applied the conservation of the isotopic field-charge spin, proven in [10], so that the two transformations executed together ensure the invariance and save the physical relevance of our theory.…”
Section: Introductionmentioning
confidence: 76%
“…Thus, one way or another, I think that quantum field theory is going to go on being very stubborn, refusing to allow us to describe all but a small number of possible worlds, among which, we hope, is ours." The above paper (together with [17]) attempted "another" way to present a predicted "possibility".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations